The Association between Mental Health Literacy and Help-Seeking Intention to Mental Well-being among Secondary School Students (in Semarang, Indonesia) - Georgius Vernon Astipa; Endang Widyorini; Daniswara Agusta Wijaya; Margaretha Sih Setija Utami; Averina Gracia Eistein Medaringo (International Journal of Health Literacy and Science, 2025)
Secondary school students often lack information on accessing mental health support, leading them to manage issues independently or with the help of family and friends. Seeking professional help is not a top priority for most adolescents. This study aims to explore the impact of mental health literacy and help-seeking intention on the mental well-being of secondary school students. In this study, 792 middle and high school students aged 12-18 completed questionnaires on the Mental Health Literacy Questionnaire – Short Version, General Help-Seeking Questionnaire, and Warwick-Edinburgh Mental Well-Being Scale. A significant correlation between mental health literacy and help-seeking intention on mental well-being of 0.258. Help-seeking intention contributed the highest correlation to mental well-being, namely 0.381, also very significant. The analysis results using multiple regression models showed that mental health literacy and help-seeking intentions affect mental well-being simultaneously (F = 64.696, p = .000). The data shows that mental well-being is only 14.1%, explained by mental health literacy and help-seeking intentions (R² = .141, p = .000). Schools and professionals can organize training programs on mental health literacy for parents, enabling them to effectively counsel their children and training selected students to become peer counselors.